SEISMIC STRATIGRAPHY OF THE BAONG AND KEUTAPANG FORMATIONS, NORTH SUMATRA BASIN - G. A. Kirby; B. Situmorang; B. Setiardja (Scientific Contributions Oil and Gas, 1990)
Examination of recently acquired seismic data in conjunction with data from boreholes in Pertamina Unit I area, North Sumatra has revealed inconsistencies in stratigraphic nomenclature. Sequences presently called Middle Baong Sandstone are broadly time equivalent to, and contiguous with the lower paris of the Keutopang sequence in the south of the area.